2014
DOI: 10.1111/epi.12581
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted anatomic white matter network in left mesial temporal lobe epilepsy

Abstract: her PhD at the University of Alberta studying white matter pathology in epilepsy. SUMMARYObjective: Brain imaging studies have shown widespread structural abnormalities in patients with temporal lobe epilepsy (TLE) within and beyond the affected temporal lobe, suggesting an altered network. Graph theoretical analysis based on white matter tractography has provided a new perspective to evaluate the connectivity of the brain. The alterations in the topologic properties of a whole brain white matter network in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 41 publications
15
80
0
Order By: Relevance
“…Previous studies have examined brain efficiency in both functional networks (Vlooswijk et al, 2011;Wang et al, 2014;Zhang et al, 2011) and structural networks in epilepsy (Bernhardt et al, 2011;Liu et al, 2014). However, these findings have remained conflicting potentially due to various factors such as different data processing approach and heterogeneous study population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined brain efficiency in both functional networks (Vlooswijk et al, 2011;Wang et al, 2014;Zhang et al, 2011) and structural networks in epilepsy (Bernhardt et al, 2011;Liu et al, 2014). However, these findings have remained conflicting potentially due to various factors such as different data processing approach and heterogeneous study population.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, 10 the same authors did not find an association between the clustering coefficient and path length measures of structural or functional connectivity with a computerized visual searching task in children with FLE. Liu et al 30 did not find any association among characteristic path length, global efficiency, and local efficiency with neurocognitive function including IQ, auditory verbal learning, and visual memory, as well as with age at seizure onset and duration of epilepsy in adults with left mesial TLE. We did not find any associations between graph network measures and IQ scores.…”
Section: Discussionmentioning
confidence: 92%
“…Differences in findings could be related to different populations of FLE, with our patient population having a wider age range and possibly more severe epilepsy relative to the patients in the study by Vaessen et al 10 Disruption in the global structural network has also been identified in childhood absence epilepsy 28 and adults with TLE. 29,30 Patients with localization-related epilepsy showed reduced regional efficiency affecting multiple regions in the frontal, temporal, and occipital lobes. Liu et al 30 also found that adult patients with left mesial TLE have significantly reduced regional efficiency in multiple regions in the temporal, frontal, and parietal lobes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations